Bioethics, spirituality and the art of taking care in the domain of health - Leo Pessini (O Mundo da Saúde, 2010)
Abstract: In this beginning of millennium, many are surprised, especially in the academic and scientific setting of the western world, before religion’s revival, or, better yet, before religions’ revival, in all domains of human life. This it is the first moment of our reflection. We present some reflexive elements later trying to better understand the movement of neurotheology. Next, we tried, in the field of religions, to identify the convergent points concerning the care of life. We then establish a relationship between the concept of health and the one of salvation. One concludes emphasizing the Camillian charisma - the care of human life subject to vulnerability coming from disease and suffering.